Effect of Socioeconomic Status on the Relationship Between Short-Term Exposure to Pm2.5 and Cardiorespiratory Mortality and Morbidity in a Megacity: The Case of Santiago de Chile - Cubillos-Montecino, F; Diaz-Robles, L; Campos-Bravo, V; Vallejo-Gallardo, F (Springer, 2020)
This work analyzes the relationship between short-term exposure to fine particulate matter and its incidence of respiratory and cardiorespiratory diseases. It involved the socioeconomic status of the population distributed in representative areas of Santiago de Chile, the capital city of Chile. The data used were collected from monitoring stations of fine particulate matter concentrations, classification of cardio-respiratory diseases, and the annual age distribution of the population in the representative areas of this megacity. Also, morbidity and mortality data and the distribution of the forecast of health by geographic zones within the Metropolitan Region were variables of input. The relative risk results showed that the level of risk from exposure to air pollution is not defined solely by the level of exposure to the pollutant when crossing the information considered. Therefore, the age distribution or quality of life of the population will define the susceptibility of this, being able to increase the risk of becoming ill or dying by being exposed to air pollution. This work showed that the exposed results serve as input data for the realization of studies in this area, regarding the cost-benefit that would be obtained by reducing pollutant emissions to the atmosphere, as well as valuable information to develop better air quality management policies. © 2020, Springer Nature B.V.